PENERAPAN PEMBERIAN GRASI TERHADAP TERPIDANA HUKUMAN MATI - Kesumadewy, Nikita; Mertha, I Ketut; Surya Darmajaya, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013, 2013)
Clemency is the forgiveness of a crime such as conversion, mutation, remission,or cancelling the executions of penalty for the suspected offenders which is granted byPresident. Clemency request applied to get law determination and fair decicion.However, in some cases, clemency is not granted by President. Especially the offendersof death penalty. Therefore, this paper will describe the reasons of clemency rejection.Besides, this paper also describes the remedies that should be taken if clemency requesthas rejected by President.
Keywords: Clemency, Death Penalty